Full length genome characterisation of Hepatitis B virus isolates at Dr George Mukhari Hospital in Pretoria, South Africa - Magobo, Rindidzani Edith (University of Limpopo (Medunsa Campus), 2011)
Introduction: Sub-Saharan Africa is a region with hepatitis B virus (HBV) hyperendemicity with more than 8% HBsAg prevalence. An estimate of two billion people has been reported to carry HBV markers. HBV was associated with about 25% of annual deaths in Africa. HBV possesses a DNA polymerase which lacks proofreading mechanism. This results in highly variability and genetic diversity which poses a challenge for the diagnosis and therapeutic management of HBV infection. High mutation rate of HBV also has great implications on the development of drug resistant mutations. Moreover, HBV diversity represents a challenge for the sensitivity of immunological and molecular diagnostic assays. A number of studies on HBV full length genome have been conducted particularly in developed countries. Limited studies are available in Africa and South Africa. In South Africa, few studies have been done analysing the complete genome of HBV isolates from patients with asymptomatic carriers and fulminant hepatitis B (Owideru et ai, 2001 a; Owideru et ai, 2001 b; Kimbi et ai, 2004; Kramvis et ai, 2002).This study was aimed at characterising the full-length genome of HBV isolates at Dr George Mukhari Hospital, Pretoria, South Africa, with a view of developing a PCR-based technology for amplification and characterisation of HBV strains with different serological profiles. The technology, if successfully developed, will contribute in understanding the molecular mechanisms resulting in various HBV variants or isolates. Methods: The study design was exploratory. Four stored serum samples collected from HBV infected patients at Dr George Mukhari hospital, Pretoria, were used to develop the molecular technology and test the hypothesis. HBV serology was previously performed targeting 5 HBV serological markers; HBsAg, anti-HBs, anti-HBc, HBeAg and anti-HBe using Elecsys version; HBV DNA quantification was done using Cobas Amplicor HBV DNA monitor assay, HBV DNA was extracted and subjected to nested PCR assay targeting HBV full length genome as two overlapping fragments: fragment A (1670 bp) and fragment B (1868 bp). The generated PCR products for both fragments were cloned into the pGEM T easy vector and 2 clones were selected from each sample. The plasm ids were purified using Invisorb@ Spin Plasmid Mini Two and the clones were recovered by PCR assay. The sample PCR products and the clone PCR products were purified and sequenced using SpectruMedix SCE2410 genetic analysis system. HBV genotyping was performed using the NCBI web-based genotyping tool. Phylogenetic analysis was done using MEGA 4 software to confirm HBV genotypes. Results: Serology results were as follows: All samples were HBsAg positive, Anti-HBs negative, anti-HBc positive and anti-HBe negative. Sample B1121 and sample 6 were HBeAg positive while samples B452 and 5 were HBeAg negative. A total of 12 PCR products were sequenced (4 study samples and 8 clones [2 clones each sample]). In total, 7 HBV full length genome sequences were deduced from this study, with 3 sequences belonging to genotype A, 2 to genotype C and 2 to genotype D. 3 HBV genotypes were detected from this study; genotype A, C and D with subgenotype A2, C1 and D1 respectively. Mutations were observed throughout the genome. In the pre-S/S open reading frame (ORF), the most significant findings were the detection of mutations within the "a" determinant site and major hydrophilic region (MHR). These mutations included Y161F,E164G observed in sample B1121 and B1121C1 belonging to subtype A1; 2 amino acid insertion at aa 161-162 in sample 5 belonging to subtype C1. Drug resistance associated mutations were identified in the polymerase gene, these included M204T and L217R which are associated with adefovir resistance, M204T also resulted in a change from tryptophan (W) to arginine (R) at aa 196 on the overlapping surface gene on sample B452 C1. Basal core promoter (BCP) and pre core/core mutations were detected in study isolates; specifically the BCP double mutation (1762/1764) was seen in 8 isolates which belonged to subtype C1 (5) and D1 (3) and the pre-core stop codon mutations (G1896A) in 4 isolates. (2 belonging to subtype C1 and the other 2 to D1). Other changes observed included a 48 nucleotides deletion in the pre-core gene, 6 nucleotides insertion in the HBx gene of all subtype D1 isolates and a 3 nucleotides deletion in subtype C1 clone. Conclusion: This study successfully optimised a PCR-based technology for the amplification and characterisation of HBV full length genome. 3 HBV genotypes were detected with subtypes A2, C1 and D1. However, the detected subtypes are rarely detected in South Africa. The detection of subtype A2 may confirm its Southern African origin. Drug resistance associated mutations were observed in this study. These included the adefovir resistance mutation which the current study confirmed it is a naturally occurring mutation as it was detected in adefovir therapy na'ive patient. The BCP and pre-core/core mutations were detected in genotype C and D isolates; however, their association with serological profile and clinical outcomes could not be deduced. Unique or novel mutations were seen in the study isolates, these included 48 nucleotides deletion in the pre core gene, 3 amino acids insertion in the RNase H and 8 amino acids deletion in the RT domain of polymerase gene. To our knowledge, these mutations have not been identified or reported in the literature. The detection of 6 nucleotide insertion in the HBx gene was reported for the first time in South African isolates. Further analysis is required to ascertain the biological significance of the unique mutations detected in this study.
Thesis (MSc. (Medical Virology))-- University of Limpopo, 2011.
Keywords: Hepatitis B virus